2005
DOI: 10.1242/jcs.02277
|View full text |Cite
|
Sign up to set email alerts
|

Homologous and heterologous reconstitution of Golgi to chloroplast transport and protein import into the complex chloroplasts of Euglena

Abstract: Euglena complex chloroplasts evolved through secondary endosymbiosis between a phagotrophic trypanosome host and eukaryotic algal endosymbiont. Cytoplasmically synthesized chloroplast proteins are transported in vesicles as integral membrane proteins from the ER to the Golgi apparatus to the Euglena chloroplast. Euglena chloroplast preprotein pre-sequences contain a functional N-terminal ER-targeting signal peptide and a domain having characteristics of a higher plant chloroplast targeting transit peptide, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…Although the presence of a signal sequence-like region was part of our selection criteria, we found no evidence in the entire database of a plastidtargeted protein that lacked a signal sequence, suggesting that in Euglena, all plastid proteins proceed to the organelle via the endomembrane system. Although some in vitro studies have suggested the potential direct import of proteins into Euglena plastids, thereby bypassing the ER (65), the bulk of relevant biochemical work indicates that transport via the endomembrane system is required for plastid targeting (38,67,(69)(70)(71). The endomembrane system is also important for plastid targeting in all protists with complex secondary plastids, including those with three (49, 55) and four (4,7,16,19,37,59,78,79) plastid membranes.…”
Section: Vol 5 2006mentioning
confidence: 99%
See 3 more Smart Citations
“…Although the presence of a signal sequence-like region was part of our selection criteria, we found no evidence in the entire database of a plastidtargeted protein that lacked a signal sequence, suggesting that in Euglena, all plastid proteins proceed to the organelle via the endomembrane system. Although some in vitro studies have suggested the potential direct import of proteins into Euglena plastids, thereby bypassing the ER (65), the bulk of relevant biochemical work indicates that transport via the endomembrane system is required for plastid targeting (38,67,(69)(70)(71). The endomembrane system is also important for plastid targeting in all protists with complex secondary plastids, including those with three (49, 55) and four (4,7,16,19,37,59,78,79) plastid membranes.…”
Section: Vol 5 2006mentioning
confidence: 99%
“…The importance of short, cytoplasm-exposed targeting motifs for intracellular sorting is well known (9). For Euglena, Sláviková et al (67) determined that this cytoplasm-exposed portion of the presequence is not required for plastid import in vitro, but they suggested that it may function in vesicle routing.…”
Section: Vol 5 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…Their ancestor must once have had a nucleomorph and transferred all essential chloroplast protein genes into its own nucleus, retargeted their proteins to the chloroplast, and then lost the nucleomorph entirely. It is possible that retargeting was easier for euglenoids, in which proteins have to cross only three membranes and the targeting machinery via Golgi vesicles that fuse with the outermost membrane copes with proteins temporarily stuck in vesicle membranes by hydrophobic sequences (14). It is widely assumed that chlorarachneans (20), there are three groups of photosynthetic eukaryotes.…”
mentioning
confidence: 99%